Studi Sistematis tentang Reaksi Pasar: Pendekatan Peristiwa dan Perilaku dalam Konteks Akuntansi - Diva Lathifah; Haidar Faiz Rabbani; Hasna Raihani Fauziyah; Khalista Ariza Saputri; Ida Farida Adi Prawira (AKUNTANSI 45, 2026)
This study explores the integration of the events approach and the behavioral accounting approach in shaping modern accounting theory. Employing a Systematic Literature Review (SLR), this research examines recent national and international publications to understand how these two perspectives can complement one another in improving the relevance and usefulness of financial reporting. The analysis reveals that the traditional value-based approach, which emphasizes aggregated outcomes such as profit and asset valuation, often fails to capture the underlying economic events behind those figures. In contrast, the events approach offers a more transparent and context-sensitive framework that reflects the dynamics of real transactions. Nevertheless, the success of this approach largely depends on how users of accounting information behave, particularly in relation to cognitive biases such as overconfidence, herding, and anchoring. The integration of event-oriented and behavioral perspectives leads to a more realistic accounting model, one that mirrors how individuals actually interpret and react to financial information. Furthermore, financial literacy and digital technology serve as key moderating factors that strengthen rational decision-making. Overall, this study contributes theoretically by presenting a conceptual framework that unites technical and psychological dimensions of accounting, and practically by providing insights for developing a more adaptive financial reporting system in today’s digital and global environment.